2013
DOI: 10.1063/1.4790173
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and energy transfer processes in ensembles and single Mn or Tb doped ZnS nanowires

Abstract: Zinc sulfide (ZnS) nanowires with a typical diameter of 100 to 300 nm have been doped with different concentrations of either Mn or Tb using ion implantation. Both systems show very efficient and long living intra-shell luminescence with strong non-exponential decay characteristics in the range of milliseconds. The time behavior of the corresponding luminescence is well described within a modified Förster model, taking into account the lower dimensionality of the nanowires in case of radiationless dipole-dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The detection was performed by a MS257 grating monochromator with an iStar intensified CCD (iCCD) camera. The gate width of the iCCD was varied between 1 μs for short times after excitation up to 1 ms for later times . Figure presents the temporal decay of the 5 D 0 → 7 F 2 emission in the ZnO nanowire matrix for samples, which were implanted to a concentration of 1 at.…”
mentioning
confidence: 99%
“…The detection was performed by a MS257 grating monochromator with an iStar intensified CCD (iCCD) camera. The gate width of the iCCD was varied between 1 μs for short times after excitation up to 1 ms for later times . Figure presents the temporal decay of the 5 D 0 → 7 F 2 emission in the ZnO nanowire matrix for samples, which were implanted to a concentration of 1 at.…”
mentioning
confidence: 99%
“…14,15 The PL spectrum of undoped ZnS nanobelts and Mn doped ZnS nanobelts also showed some emission bands at 440 and 540 nm, which were assigned to defects produced by S and Zn vacancies, respectively, while the emission band observed at 590 nm in Mn doped ZnS was attributed to Mn d-d state transition. [16][17][18] It was also observed that the defect related emission decreased as Mn concentration increased in Mn-doped ZnS nanobelts. In the case of Cu-doped ZnS nanorods green emission was attributed to elemental S species present on the nanorod surface, and orange emission was associated with recombination of electrons at deep defect levels of Cu introduced states.…”
Section: Introductionmentioning
confidence: 93%